Subacute sclerosing panencephalitis with disorganized behavior: a case report from psychiatry ward (Bangladesh Journal of Psychiatry, 2024)
Subacute sclerosing panencephalitis (SSPE) is a late onset, rare and slowly progressive viral encephalitis with a mandatory fatal outcome. The disease initially presents with myoclonic jerks and seizures, ocular manifestations, cognitive decline and behavioral disturbances.  However, few rare cases of SSPE had been reported with the initial presentation of sole psychiatric symptoms creating a diagnostic dilemma. We hereby reported a case of an 18 years-old male presented with a history of disorganized behavior who was further evaluated as a case of SSPE. The importance of a holistic approach to rule out organic causes before diagnosing a psychiatric disorder had been highlighted in this report.Bang J Psychiatry 2023;37(2): 49-51